The optimal bowel preparation intervals before colonoscopy: A randomized study comparing polyethylene glycol and low-volume solutions. Issue 3 (March 2018) - Kojecky, Vladimir; Matous, Jan; Keil, Radan; Dastych, Milan; Zadorova, Zdena; Varga, Michal; Kroupa, Radek; Dolina, Jiri; Misurec, Miroslav; Hep, Ales; Griva, Martin
Abstract: Background & aims: The optimal duration of bowel preparation has only been assessed for polyethylene glycol (PEG). The aim of the study was to determine the intervals for achieving a satisfactory quality/tolerability of the preparation using PEG/ascorbic acid (PEGA) and sodium picosulphate/magnesium citrate (SPMC), and to compare them with 4L of PEG. Methods: A randomized, endoscopist-blinded, multicentre study. The 612 outpatients referred to a colonoscopy, were prepared using PEG, SPMC, PEGA. The quality, tolerability, duration of the preparation, and the interval from the end of the preparation to the colonoscopy was assessed. Results: Optimum duration of the preparation was similar for both PEG and SPMC (≥7.3 vs. ≥8.8 h, overall ≥8.4 h). Optimum interval to the colonoscopy was ≤11.8 h and did not differ between preparations (PEG, PEGA ≤ 11.8, SPMC ≤ 13.3 h). These times were the only predictors for a satisfactory preparation. The tolerability depends on the product type (SPMC) only. Timing of the preparation or the other factors had no impact on tolerability. Conclusion: The optimum intervals for bowel preparation are identical for all preparations. Satisfactory preparation is achived at the preparation length ≥8.4 h and the time to colonoscopy ≤11.8 h.